Characterization of Naegleria fowleri from two human cases: insights into its excretion/secretion products - Chacón Camacho, Natalia; Steller Espinoza, María Fernanda; Alvarado-Ocampo, Johan; Osuna, Antonio; Retana Moreira, Lissette; Abrahams Sandí, Elizabeth (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionNaegleria fowleri is the etiologic agent of primary acute meningoencephalitis (PAM). Although this amoeba is commonly found in water and soil, reports of infections are rare; problems with diagnosis probably contribute to underestimation. Moreover, information regarding the pathogenicity of this species is still lacking. Costa Rica reported the first three cases of PAM during 2020; from these, two N. fowleri isolates were recovered. The aim of this study was to characterize and compare these isolates, focusing in excretion/secretion products.MethodsAnalyses of protein profiles by silver staining and protease activity assays were performed to characterize whole protein extracts and conditioned media from isolates. Proteomic analyses of excretion/secretion products, including extracellular vesicles (EVs), were performed, and cytopathic effect and drug susceptibility tests were also compared between isolates.ResultsResults obtained were similar for both isolates. Patterns of multiple bands were observed in each isolate after silver staining. Proteomics analyses revealed a total of 88 and 62 non-redundant proteins as part of the cargo of EVs secreted by trophozoites of N. fowleri Guanacaste and N. fowleri Limón, while conditioned media results revealed 34 and 17 non-redundant proteins, respectively; hydrolase activity and actin filament binding were part of the most represented gene ontology terms in EVs and conditioned media. Regarding drug susceptibility assays, no statistically significant differences were identified. On the other hand, although protease activity resulted very similar with substrate buffer at pH 8.5, only N. fowleri Limón showed activity between 40 and 70 kDa at pH 5.0; in contrast, a more rapid cytopathic effect was observed when incubating Vero cells with N. fowleri Guanacaste.DiscussionComparative analyses of different N. fowleri isolates, supported by their remarkable genomic heterogeneity that could be reflected in different metabolic repertoires, are key to understanding virulence and pathogenicity of this amoeba, and could help to explain whether different isolates differ in the severity or course of PAM.